Practical three-way calibration - Olivieri, Alejandro; Escandar, Graciela M. (Amsterdam : Elsevier, 2014)
Practical Three-Way Calibration is an introductory-level guide to the complex field of analytical calibration with three-way instrumental data. With minimal use of mathematical/statistical expressions, it walks the reader through the analytical methodologies with helpful images and step-by-step explanations. Unlike other books on the subject, there is no need for prior programming experience and no need to learn programming languages. Easy-to-use graphical interfaces and intuitive descriptions of mathematical and statistical concepts make three-way calibration methodologies accessible to analytical chemists and scientists in a wide range of disciplines in industry and academia. Numerous detailed examples of slowly increasing complexity Exposure to several different data sets and techniques through figures and diagrams Computer program screenshots for easy learning without prior knowledge of programming languages Minimal use of mathematical/statistical expressions.
7.1 An apparent contradiction7.2 Description of the data set; 7.3 PARAFAC study of a test sample; 7.4 Increasing the number of PARAFAC components; 7.5 Study of the remaining samples; 7.6 Other separation data and what to do; 7.7 A PARAFAC variant for chromatographic data; 7.8 PARAFAC2 calibration with the LCDAD_data; 7.9 Chromatographic alignment; 7.10 Homework; References; Chapter 8 -- Multivariate Curve Resolution-Alternating Least-Squares; 8.1 Multivariate curve resolution-alternating least-squares; 8.2 Estimating the number of components; 8.3 MCR-ALS initialization; 8.4 Constraints.
Print version record.
Includes bibliographical references and index.
Keywords: Chemometrics; Calibration; SCIENCE -- Chemistry -- Analytic; Calibration; Chemometrics; Electronic books